Underutilization of surgical resection in patients with pancreatic acinar cell carcinoma. Issue 6 (June 2019) - Landa, Karenia; Freischlag, Kyle; Nussbaum, Daniel P.; Youngwirth, Linda M.; Blazer, Dan G.
Abstract: Background: Pancreatic acinar cell carcinoma (pACC) is a rare malignancy and surgical utilization has been historically low in these patients. Contemporary outcomes for this patient population remain unknown. Methods: The 1998–2012 National Cancer Data Base was queried for baseline characteristics in patients with pACC. Patients with potentially operable disease (stage I/II) were grouped by surgical resection. Multivariable logistic regression was used to predict factors associated with resection. Survival was estimated using Kaplan–Meier analysis. A proportional hazards model identified factors associated with overall survival. Results: 980 patients were identified. Mean age at diagnosis was 64 years. Tumors were more common in men (68%), white patients (88%), and within the pancreatic head (57%). Thirty-four percent of patients with localized disease failed to undergo resection. Five-year survival was higher among patients who underwent resection (42% vs. 9%, p < 0.001). In patients with resectable disease, male sex, older age, black race, tumors within the pancreatic head, lower grade tumors and treatment at non-academic centers are associated with failure to undergo surgery. Conclusion: Patients with localized pACC have increased survival after resection. However, in this contemporary analysis, resection continues to be underutilized and new efforts to increase resection rates should be undertaken.